PENGARUH KONDISI KEUANGAN PERUSAHAAN, UKURAN PERUSAHAAN, OPINI AUDIT TAHUN SEBELUMNYA DAN PREDIKSI KEBANGKRUTAN TERHADAP AUDIT DELAY - Sekar Prabandari (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
This research was conducted with the aim of knowing how the influence of the company's financial condition, company size, previous year's opinion, and bankrupty prediction on audit delay in manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017. The method used in this research is descriptive verification. The population in this study were 157 manufacturing companies in the study period from 2013 - 2017. The research sample was 98 companies using purposive sampling method, namely sample collection techniques with certain considerations. Data obtained from the Indonesia Stock Exchange. The data analysis used in this research is multiple regression analysis. Analysis of research data processing using SPSS 25 software. The results of the research variables of the company's financial condition affect the audit delay opinion. Meanwhile, company size, previous year's opinion and bankruptcy prediction had no significant effect on audit delay opinion. Simultaneous testing shows that the company's financial condition, company size, previous year's audit opinion, and the prediction of company bankruptcy have a significant effect on audit delay opinion.